2001
DOI: 10.1530/eje.0.1440283
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IGF binding protein-1 is inversely associated with leptin in non-obese men and obese postmenopausal women

Abstract: Objective: Hyperleptinaemia and hyperinsulinaemia interrelate to insulin-like growth factor binding protein 1 (IGFBP-1), and disturbances in the growth hormone±IGF-I axis are linked to obesity and cardiovascular diseases. However, whether the association between leptin and the GH±IGF-I axis is altered with increasing obesity is not known. We therefore examined the relationship between leptin, IGF-I, IGFBP-1, insulin and proinsulin in men and women with or without obesity in a population study. Design and subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…We also observed that differences in median levels of IGFBP-1 and the OR (10th percentile) are slightly higher in women than men. A recent study by Söderberg et al (15) showed similar results with regard to IGFBP-1 levels, further supporting these findings. Like the Bedford survey of CHD (16), our data indicated no gender differences between serum levels and MI risk inferred by high levels of serum insulin and HOMA.…”
Section: Igfbp-1 (Or (95% Ci))supporting
confidence: 70%
“…We also observed that differences in median levels of IGFBP-1 and the OR (10th percentile) are slightly higher in women than men. A recent study by Söderberg et al (15) showed similar results with regard to IGFBP-1 levels, further supporting these findings. Like the Bedford survey of CHD (16), our data indicated no gender differences between serum levels and MI risk inferred by high levels of serum insulin and HOMA.…”
Section: Igfbp-1 (Or (95% Ci))supporting
confidence: 70%
“…33 Several studies have examined the associations between leptin and IGF-1 and IGFBP-3. [40][41][42][43] We observed a statistically significant interaction between LEP polymorphisms and both IGF1 and IRS2 genotypes. Those without a 19 CA repeat of the IGF1 gene had the greatest reduction in risk of colon cancer if they also had the AA genotype of the rs2167270 LEP gene.…”
Section: Discussionmentioning
confidence: 60%
“…The hepatic production of IGFBP-1 is downregulated by insulin (13). Accordingly, in the general population, there is a correlation between low levels of IGFBP-1 and hyperinsulinemia, and these findings may link to an increased cardiovascular risk (14,15). However, IGFBP-1 concentrations rise during the development of type 2 diabetes, despite persisting hyperinsulinemia, indicating increased hepatic insulin resistance during disease progression (16,17).…”
mentioning
confidence: 99%